Epigenetic remodeling by sex hormone receptors and implications for gender affirming hormone therapy - Celestra, Den; Nguyen, Nhi N. L.; Laberthonniere, Camille; Pang, Ken C.; Saffery, Richard; Davey, Rachel A.; Mhlanga, Musa; Cheung, Ada S.; Novakovic, Boris (Frontiers in Immunology, 2025)
Sex differences in immune system development and response to pathogens has been well documented, with females exhibiting more favorable outcomes for certain infections but a higher incidence of autoimmune disease compared to males. At least some of these sex differences are mediated by sex hormones, which signal through sex hormone receptors to remodel the regulatory chromatin landscape of cells. Here, we summarize the current knowledge of how sex hormone receptors remodel chromatin structure and epigenetic marks in different contexts in humans. As the epigenome is fundamental to specifying cell identity and function, and reflects past exposures, epigenetic variation can influence cellular responses to future stimuli. This has implications for susceptibility to infection and complex inflammatory disease in a range of hormone therapy settings, including gender-affirming hormone therapy in transgender people. Therefore, profiling of epigenetic marks in the context of gender-affirming hormone therapy is an important unexplored field of research.